2013
DOI: 10.1155/2013/659232
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Clinical, Hormonal and Morphological Studies in Patients with Neuroendocrine ACTH-Producing Tumours

Abstract: This paper highlights the problem of neuroendocrine tumours (NETs) with clinical symptoms of hypercorticism caused by hypersecretion of adrenocorticotropic hormone (ACTH) by tumour cells. In most cases (85%), the tumours were localized in the pituitary gland (Cushing's disease); 15% of the patients had an extrapituitary tumour that manifest as an ectopic ACTH secretion (EAS). Comparative analysis of clinical, hormonal, histological, and immunohistochemical characteristics of pituitary and extrapituitary ACTH-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 16 publications
0
8
0
6
Order By: Relevance
“…ii) Ectopic tumors may secrete ACTH or an ACTH analogue and a simple anti-ACTH antibody is insufficient for detecting ectopic secretion. iii) Some lesions may secrete ACTH and corticotropin-releasing hormone (CRH) simultaneously (10). Moreover, Al-Gahtany et al (11) reported three cases of ectopic CRH tumors, with pituitary hyperplasia leading to high corticotrophin hyperlipidemia; they also reported that, postoperatively, the ACTH level immediately returned to normal if the tumor produced ACTH, but it decreased gradually if the tumor produced CRH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ii) Ectopic tumors may secrete ACTH or an ACTH analogue and a simple anti-ACTH antibody is insufficient for detecting ectopic secretion. iii) Some lesions may secrete ACTH and corticotropin-releasing hormone (CRH) simultaneously (10). Moreover, Al-Gahtany et al (11) reported three cases of ectopic CRH tumors, with pituitary hyperplasia leading to high corticotrophin hyperlipidemia; they also reported that, postoperatively, the ACTH level immediately returned to normal if the tumor produced ACTH, but it decreased gradually if the tumor produced CRH.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who receive comprehensive treatment, including completion of chemoradiotherapy, are expected to have longer tumor-free survival, compared with those receiving surgery alone (10). Drugs focusing on the epithelial component may also be selected.…”
Section: Discussionmentioning
confidence: 99%
“…This makes early diagnosis much more important. IPSS is the most reliable examination for ECS, but it may not be feasible in many institutes 3, 10. Complete imaging examination, related blood and urine tests, low dose and high dose dexamethasone tests, immunohistochemical characteristics, and cell proliferation potential (Ki‐67) should be considered when suspicious of ECS.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there are EAS patients in whom the negative feedback after high dose of dexamethasone is preserved (similarly to ACTH-secreting pituitary gland adenoma cases). This is mainly observed in patients with bronchial NENs [7,27]. The ACTH concentration measurement is a significant laboratory problem because this hormone is a thermally unstable protein, and therefore laboratory assessment should be performed immediately after the blood sample was acquired (to limit the possibility of false negative results).…”
Section: Szkolenie Podyplomowementioning
confidence: 99%
“…W grupie chorych z przysadkowym CS szacowanej na 10-20% przypadków, stwierdza się, podobnie jak u pacjentów z EAS brak hamowania po dużej dawce deksametazonu [26]. Z drugiej strony opisano hiperkortyzolemię u chorych z EAS, gdzie zachowane było ujemne sprzężenie zwrotne po zastosowaniu dużej dawki deksametazonu, podobnie jak w postaci przysadkowej CS, głównie u chorych z NEN oskrzeli [7,27]. Problem dotyczy również oznaczenia ACTH.…”
unclassified